Sermons translated from the original French of the late Rev. James Saurin, pastor of the French church at the Hague - Saurin, Jacques (W.J. M'Cartee, 1813)
v. 1. On the attributes of God.--v. 2. On the truth of revelation.--v. 3. On the principal doctrines of Christianity.--v. 4. On Christian morality.--v. 5. On various subjects.--v. 6. On sacramental occasions.--v. 7. On important subjects.--v. 8. On various subjects: with a general index.